Sound Correspondences among Cognates Shared by Arabic, English, and Indonesian - Fauzi Syamsuar (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
This article investigates sound correspondences among cognates shared by Arabic (ARA), English (ENG), and Indonesian (IND). The cognates comprise ARA and IND words copied from ENG and ENG words as the forms from which they are copied. The data corpora are taken from the phonological forms (pronunciations) of the words which are obtained from reliable transcription/source. Besides sound correspondences (known as sound replacements in morphophonemics), certain other morphophonemic phenomena found in the phonological realizations of the words, i.e., sound additions, sound fusions and deletions, sound laxings, sound lenitions, sound fortitions, assimilations, dissimilations, and metatheses, are being analytically discussed. The patterns of sound correspondences among the cognates become the findings of the investigation.